2007
DOI: 10.1128/iai.01326-06
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-2-Mediated C-C Chemokine Receptor 3 and Eotaxin-Driven Eosinophil Influx Induced by Mycobacterium bovis BCG Pleurisy

Abstract: An acute and persistent eosinophil infiltration is observed during Mycobacterium bovis BCG pleural infection in mice. Eosinophil accumulation, lipid body formation, and eotaxin production were significantly reduced in BCG-infected Toll-like receptor-2 (TLR2)-deficient mice compared to wild-type mice. Neutralization of eotaxin or CCR3 drastically inhibited BCG-induced eosinophil accumulation and lipid body formation, indicating that BCG-induced eosinophil recruitment and activation is largely dependent of TLR2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…The role of TLR-mediated pathogen recognition and activation in the mechanism of lipid body formation has been documented (4,5,28,32). The role of TLR2 in regulating PPAR␥ expression during BCG infection in vitro was investigated.…”
Section: Induction Of Ppar␥ Expression By Bcg Infection Depends On Tlmentioning
confidence: 99%
“…The role of TLR-mediated pathogen recognition and activation in the mechanism of lipid body formation has been documented (4,5,28,32). The role of TLR2 in regulating PPAR␥ expression during BCG infection in vitro was investigated.…”
Section: Induction Of Ppar␥ Expression By Bcg Infection Depends On Tlmentioning
confidence: 99%
“…Specifically in macrophages, it has been shown that the genesis of new lipid bodies can be evoked by a variety of inflammation-related stimuli, including oxidized low-density lipoprotein (oxLDL) and oxLDL-components (but not native LDL) acting through membrane and nuclear receptors (9 -12). Pathogens including Grampositive (Mycobacterium bovis bacillus Calmette-Guérin) and Gram-negative bacteria (Escherichia coli) (13)(14)(15)(16), Chlamydia pneumoniae (17) and Trypanosoma cruzi (18), as well as pathogen-related molecules (LPS and lipoarabinomannan) (13,14) acting through their specific receptors (CD14, TLR4, and TLR2) (13,14) were also shown to elicit signaling that culminate with activation of ER-assembling lipid body machinery. Downstream to the activation by pathogen-derived molecules, endogenous molecules-yet to be characterized-may also trigger lipid body biogenesis during infection-driven inflammation therefore comprising potential therapeutical targets for lipid body regulated pathologies.…”
mentioning
confidence: 99%
“…7 In other models of pathogen-induced eosinophilia, it has been shown that direct stimulation of TLR2 by M. bovis can induce an eosinophilic infiltration into the pleural cavity that is highly dependent on IL-5, CCL11, and the CCL11 receptor CCR3. 28 Our results suggest that TLR2-mediated eosinophil recruitment also occurs in the gastrointestinal tract, potentially as a result of exposure of effector cells to products of the bacterial flora.…”
Section: Discussionmentioning
confidence: 66%
“…27 Stimulation of TLR2 by Mycobacterium bovis has also been shown to induce an eosinophilic infiltration into the pleural cavity that is highly dependent on IL-5, CCL11, and CCR3 (a CCL11 receptor). 28 The role of TLR2 in eosinophil recruitment during DSS colitis and the potential role of eosinophils in the severe colitis seen in TLR2 Ϫ/Ϫ mice have not been previously examined.…”
mentioning
confidence: 99%